Ukbe B. Âmir El-Cühenî’nin hayatı ve rivâyetleri - Kandıralı, Yakup (My University, 2019)
Ukbe b. Âmir el-Cühenî Müslüman olmadan önce Medine’de koyun sürüsünü otlatarak yaşayan bir çobandı. Hz. Peygamber Medine’ye hicret ettiğinde onunla ve İslâm’la tanıştı. İslâm’a girdikten sonra zaman zaman Hz. Peygamber’e gelerek onun meclislerine katıldı. Daha sonra Medine’de Ashâb-ı Suffe’nin arasında yer aldı. İlme olan merakı nedeniyle Hz. Peygamber’den uzun süre ilim tahsil etti. Kur’ân, hadis, fıkıh ve ferâiz ilimlerine vâkıf âlim bir şahsiyet oldu. Bir yandan kadı olarak aralarında anlaşmazlık bulunan insanların davalarına bakarkenbir yandan da Tebük gazvesi, Dımeşk ve Mısır’ın fethi gibi savaşlara katıldı. Hz. Peygamber’den rivayet ettiği hadislerin tamamı güvenilir hadis kaynaklarında yer almaktadır. Bu çalışmada rivâyetlerinin çoğunluğunun sahih isnadlarla nakledildiği ve râvilerinin de güvenilir oldukları ortaya çıkmıştır.

Before converting to Islam, Ukba b. Amir al-Juhani lived in Madina as a shepherd grazing a herd of sheep. He met the Holy Prophet (pbuh) and Islam following the Prophet’s migration to Madina. He became Muslim and accordingly a companion to the Holy Prophet (pbuh). Having become a Muslim, he occasionally took part in the communion of the Holy Prophet (pbuh). Later on, he became a member of the inhabitants of as-Suffa. On account of his curiosity for knowledge, he incessantly studied Islam under the guidance of the Holy Prophet (pbuh). He gradually became a scholar in Qur’an, Hadith, Fıkh and Farâiz (law of inheritance). As a judge, he ruled about disputes involving disagreements between individuals. As a brave soul of Jihad, he took part in Tabuk campaign led by the Holy Prophet (pbuh) as well as the conquest of Damascus and Egypt. He recounted ahadiths from the Holy Prophet (pbuh) as a narrator. All of these ahadiths were recorded in reliable hadith resources. This study has illustrated that most of the ahadiths which al-Juhani recounted are valid and that the narrators which indicated are trustworthy.
Keywords: companions; governor of Egypt; Hadis; Hadith; Islam; İslam; Mısır valisi; narration; râvi; rivâyet Ukba b. Amir al-Juhani; sahâbe; Suffa; Suffe; transmitter; Ukbe b. Âmir el-Cühenî